2008
DOI: 10.5713/ajas.2008.80057
|View full text |Cite
|
Sign up to set email alerts
|

The Growth-promoting Effect of Tetrabasic Zinc Chloride is Associated with Elevated Concentration of Growth Hormone and Ghrelin

Abstract: An experiment was conducted to investigate the mechanism for the effect of tetrabasic zinc chloride (TBZC) in enhancing growth performance of weanling piglets. Gut-brain peptides play an important role in the regulation of growth and appetite in animals. This study evaluated the effects of TBZC on blood concentrations of growth hormone (GH), ghrelin, insulin-like growth factor-I (IGF-I), cholecystokinin (CCK) and neuropeptide Y (NPY). Seventy-two weanling piglets (Landrace×Large White) with an initial body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…These results suggested that 1,600 mg/kg ZnO may not be sufficient to improve the growth performance and health status of weaned piglets. Additionally, serum GH and IGF-I levels were significantly increased in TBZC group, which was partially agreed with Zhang and Guo ( 25 ) that the levels of serum GH and Ghrelin were improved when 2,000 mg Zn/kg from TBZC was fed to piglets. Therefore, compared with traditional ZnO, TBZC can improve the growth performance of piglets with a lower dose.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results suggested that 1,600 mg/kg ZnO may not be sufficient to improve the growth performance and health status of weaned piglets. Additionally, serum GH and IGF-I levels were significantly increased in TBZC group, which was partially agreed with Zhang and Guo ( 25 ) that the levels of serum GH and Ghrelin were improved when 2,000 mg Zn/kg from TBZC was fed to piglets. Therefore, compared with traditional ZnO, TBZC can improve the growth performance of piglets with a lower dose.…”
Section: Discussionsupporting
confidence: 87%
“…TBZC has been shown to reduce intestinal permeability and improve mucosal barrier function ( 9 ). Dietary TBZC supplementation also involved in stimulating the secretion of ghrelin and growth hormone, thereby promoting muscle protein synthesis and cell proliferation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reynolds et al [ 52 ] found that, when pigs weaned at day 28 were given the choice between a Zn unsupplemented diet and a diet supplemented with 3100 mg Zn/kg (as ZnO), up to 91 % of the total feed consumption was of the unsupplemented diet. Zhang and Guo [ 53 ] and Yin et al [ 54 ] found a higher concentration of circulating ghrelin in pigs (24–28 days of age) fed a 2000 mg Zn/kg diet compared to a 100–130 mg Zn/kg diet. Ghrelin secreted from enteroendocrine cells of the gastrointestinal tract is involved in appetite regulation, and increased ghrelin secretion stimulates appetite [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…TBZC or ZnO replaced wheat bran in the diet. The experiment lasted 14 d. Hahn & Baker ( 2 ) showed that ZnO can improve the daily gain of weaning pigs, while our previous studies demonstrated similar effects of ZnO and TBZC on the performance of weaning pigs ( 5 , 6 ) . Therefore, ZnO and TBZC were selected as two dietary Zn sources in the present study.…”
Section: Methodsmentioning
confidence: 95%